A View of Julien Sorel, the Protagonist of "The Red and the Black" with Reference to Søren Kierkegaard’s "The Concept of Irony" - Barthelme, B. (KIERKEGAARDIANA, 1977)
A View of Julien Sorel, the Protagonist of "The Red and the Black" with Reference to Søren Kierkegaard’s "The Concept of Irony"